Australian Middle Eastern parents' perceptions and practices of children's weight‐related behaviours: Talking with Parents' Study. (30th April 2015) - Hardy, Louise L.; Hector, Debra; Saleh, Shay; King, Lesley
Abstract: The home environment is associated with obesity‐related behaviours among children, and research in Australia has shown that some of these behaviours are more prevalent among children from particular cultural backgrounds including Middle Eastern. This study presents findings from face‐to‐face, semi‐structured interviews conducted in April 2013 with a convenience sample of Middle Eastern parents of primary school‐age children at an Islamic private school in Sydney, Australia. The interviews explored parental perceptions and practices regarding state government health messages addressing children's eating, physical activity and screen time. The purpose of the study was to investigate whether the content of these generic public health messages is relevant and acceptable to Middle Eastern parents of young children, and to identify any enablers and barriers to adopting these healthy practices at home. Thematic analysis identified predominant themes. In total, 21 interviews were conducted (reference children: 12 boys/9 girls, aged 5–12 years). The content of current health messages regarding children's weight‐related behaviours was familiar to respondents, and accepted as relevant for guiding their parenting practices. Parents perceived that they typically encouraged healthy behaviours, although they also reported making regular exemptions, in response to various circumstances. Overall, the perceptions and reported practices of the parents were consistent with other studies with Australian parents. There were no apparent culturally specific barriers or enablers to children's weight‐related behaviours. There is however scope for health promoters to provide more precise information on health recommendations, health risks and benefits, and to provide more specific ideas for ways in which parents can act on these health messages within the home and family environment, to encourage and support healthy behaviours in their children.